Trends of intangibles and intellectual capital: State of art and research - Matos, F. (2019)
Conference proceedings about intellectual capital and knowledge management are important sources of current ideas about intellectual capital, intangibles, knowledge management, authors, institutions, trends and how these are related. Since those meetings are periodic concentrations of the main sources - the papers' authors - of innovative ideas about those subjects, it is believed that an adequate analysis and synthesis of those documents can be useful to identify emerging concepts, topics, trends, directions and relations involving those concepts, their creators and the places where they were presented. The purpose of this paper is to provide, using as a data source the texts of conference proceedings, a comprehensive knowledge about the state of art of the research on intangibles and intellectual capital overthe last decade and to identify the trends on those issues for future research. This study consists of a review of abstracts, titles, authors' names, emails and institutions, keywords and main texts of all the papers in the Proceedings of the European Conference on Intellectual Capital, presented between 2009 and 2017. The study also involves the identification and characterization of patterns, such as the main topics subjacent to such texts, including associations of concepts, and the trends of such associations, involving concepts of intellectual capital and intangibles, throughout that period and conference locations. The innovative methodology used in this study is text mining, based on the classic bag-of-words model and in more recent natural language processing approaches, incorporated in R or Python packages. This work also highlights some needs not covered by the present packages and presents directions for future researches and software development. The paper can be classified as a pilot study to support the construction of new computational and knowledge management methodologies in this area.